Use of mining wastes in asphalt concretes production - Medina García, L.; Betancourt, S.; Rodríguez, E.; Martins Ribeiro, L.F.; Muniz de Farias, M. (Revista Ingeniería de Construcción, 2023)
waste from the exploitation and processing of nickel laterites in Cuba and Brazil, the work takes as a hypothesis that, if it demonstrates the real possibility of using such waste as a partial substitute for aggregates in the production of asphalt concrete, the negative environmental impact caused by them in the places where they are deposited could be reduced. The objective of the work is, to demonstrate the suitability of mining waste from nickel and cobalt processing dams in the municipalities of Moa and Nicaro, in the province Holguín, Cuba. Such wastes come from Ammonium Carbonate Leaching and Pressurized Acid Leaching processes. The research methodology it has based on taking representative samples from the waste dams, their subsequent physical, chemical and mineralogical characterization, and the characterization of the aggregates and asphalt cement used in the mixtures under study. The design of the asphalt concrete mixtures was carried out using the Marshall method. Subsequently, a comparative analysis was made on the behavior of the asphalt concretes made with limestone and mining waste fillers investigated. It´s demonstrated, from the results of the laboratory tests, that it is possible to manufacture asphalt concretes with the use of mining residues from the processing of nickel laterites from Moa and Nicaro, satisfactorily fulfilling the required technical parameters.